(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: “Brain drain” is defined as the migration of educated and highly skilled professionals to developed countries, especially in pursuit of better opportunities. The objective of this study was to determine the career intentions of medical undergraduates and their influencing factors. Subjects and methods: A descriptive cross-sectional study was conducted after approval from the Institutional Research Committee from May to September 2023 with no IEC/244-23. By using non-probability convenience sampling, all 3rd, 4th, and final years MBBS were included in the study as a whole sample of 350. Data was collected with the help of a closed-ended questionnaire. Additionally, the Quality-of-Life Scale (WHOQOL-Bref), designed by the World Health Organization, and the Perceived Stress Scale-14 (PSS-14) were used. Data was analyzed in IBM SPSS version 25. Descriptive statistics, Chi-square, T test, and Pearson correlation were used for analysis, and a p-value of ≤ 0.05 was considered significant. Results: In this study, 53.8% of the participants were female (n=188) while 46.2% (n=162) were male, with the mean age of 23.05 ±1.45 years. Most of the students were unsatisfied after choosing the medical field (55.8%, n=195). The PSS-14 score mean was 1.88±0.48, and it was found that those participants who thought of practicing abroad were not statistically different from those who wanted to work in this country. After applying the Pearson correlation test between the WHOQOL-Bref and PSS-14 scores, it was found it be significant and negative (r=-0.520, p<0.05). Conclusion: The study’s results indicate that the majority of medical students intend to pursue their careers abroad. Key factors contributing to this decision include long working hours, physical/verbal violence, and mobbing in their workplace